Petrographically quantifying the damage to field and lab-cast mortars subject to freeze-thaw cycles and deicer application - Qiao, Chunyu; Hosseinzadeh, Nima; Suraneni, Prannoy; Wei, Sihang; Rothstein, David (Journal of infrastructure preservation and resilience, 2021)
Although calcium oxychloride (Ca-Oxy) is known to damage cementitious materials exposed to calcium chloride (CaCl 2 ) deicers, there is little direct observation of Ca-Oxy in the field due to its instability. This paper uses optical microscopy (OM) and scanning electron microscopy coupled with energy dispersive X-ray spectrometry (SEM-EDX) to detect the formed Ca-Oxy and quantify its associated damage in a field mortar subject to freeze-thaw cycles and deicer application. The characterized damage in the field mortar is compared to that in lab-cast portland cement paste and mortar which are submerged in a CaCl 2 solution of 25 wt.% under freeze-thaw cycles (− 8 to 25 °C). The field and lab-cast mortars show similar cracking patterns that are parallel to the exposure surface with a variation of 30–45° in the preferred orientation due to the constraints of sand particles. During each lab-controlled freeze-thaw cycle, the high CaCl 2 concentration of 25 wt.% stabilizes the formed Ca-Oxy, which continually damages the mortar and eventually results in 3–4 times higher crack density compared to that in the field mortar. SEM-EDX analysis confirms the presence of secondary deposits including Friedel’s salt, ettringite and Ca-Oxy. Image analysis on thin section photomicrographs shows a reduction of 86.4% in calcium hydroxide (Ca(OH) 2 ) content in the damaged field mortar compared to the undamaged field mortar, suggesting significant leaching of Ca(OH) 2 to form Ca-Oxy due to the deicer application.